2018
DOI: 10.1007/s00408-018-0151-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Anti IL-4, IL-5 and IL-13 Drugs for Treatment of Eosinophilic Asthma: A Network Meta-analysis

Abstract: All drugs except for tralokinumab showed improvements in FEV, ACQ, and AQLQ. Only reslizumab and dupilumab were associated with statistically significant reductions in asthma exacerbation rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 48 publications
2
21
0
Order By: Relevance
“…Activation of IL‐4 is also significant in enhancing IgG1 and IgE generation in asthma (Barnes, 2008). During the asthma process, IL‐5 is capable of controlling eosinophil formation and proliferation, IgE secretion in asthma elicited by IL‐4 can also be enhanced by IL‐5 (Iftikhar, Schimmel, Bender, Swenson, & Amrol, 2018). As a classic inflammatory cytokine, IL‐6 promotes IL‐4 generation and modulates the Th1/Th2 balance toward Th2, thus enhancing Th2 differentiation and reducing Th1 cell differentiation (Dienze & Rincon, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of IL‐4 is also significant in enhancing IgG1 and IgE generation in asthma (Barnes, 2008). During the asthma process, IL‐5 is capable of controlling eosinophil formation and proliferation, IgE secretion in asthma elicited by IL‐4 can also be enhanced by IL‐5 (Iftikhar, Schimmel, Bender, Swenson, & Amrol, 2018). As a classic inflammatory cytokine, IL‐6 promotes IL‐4 generation and modulates the Th1/Th2 balance toward Th2, thus enhancing Th2 differentiation and reducing Th1 cell differentiation (Dienze & Rincon, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Among these Th2 cytokines, IL-4 promotes the differentiation, proliferation, and activation of B cells; induces inflammatory cells eosinophils to infiltrate into the lung tissue; and increases the levels of IgE and IgG1 in serum (Barnes, 2008). IL-5 can control the formation and proliferation of eosinophils and enhances the IL-4-induced IgE secretion during asthma (Iftikhar, Schimmel, Bender, Swenson, & Amrol, 2018). In addition, IL-13 promotes the differentiation of B cells and directly induces an inflammatory reaction and AHR in the lungs of asthmatic mice (Karo-Atar, Bitton, Benhar, & Munitz, 2018;Lightwood et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Quality of life scores were improved but not to a clinically significant extent. No head‐to‐head trials have been reported; indirect comparisons have produced different conclusions about relative efficacy …”
Section: Efficacy Of Monoclonal Antibodies For Asthmamentioning
confidence: 99%